Diagnosis and treatment based on quantitative PCR after controlled human malaria infection. (December 2016) - Walk, Jona; Schats, Remko; Langenberg, Marijke; Reuling, Isaie; Teelen, Karina; Roestenberg, Meta; Hermsen, Cornelus; Visser, Leo; Sauerwein, Robert
Abstract Background Controlled human malaria infection (CHMI) has become well-established in the evaluation of drugs and vaccines. Anti-malarial treatment is usually initiated when thick blood smears are positive by microscopy. This study explores the effects of using the more sensitive qPCR as the primary diagnostic test. Methods 1691 diagnostic blood samples were analysed by microscopy and qPCR from 115 volunteers (55 malaria naïve and 60 having received chemoprophylaxis and sporozoite immunization) who were challenged by five mosquitoes infected withPlasmodium falciparum sporozoites of the NF54 strain. Results Retrospective analysis of different qPCR criteria for diagnosis and treatment, showed that once daily qPCR (threshold 100 parasites/ml) had 99 % sensitivity and 100 % specificity, and shortened the median prepatent period from 10.5 to 7.0 days after CHMI when compared to twice daily measurement of thick blood smears (threshold 4000 parasites/ml). This is expected to result in a 78 % decrease of adverse events before initiation of treatment in future studies. Trial outcome related to infection and protective efficacy remained unchanged. Conclusion The use of qPCR as the primary diagnostic test in CHMI decreases symptoms as well as parasitaemia while obviating the need for twice daily follow-up. The implementation improves safety while reducing the clinical burden and costs without compromising the evaluation of protective efficacy.